Source-Agnostic Single-Ended Protection and Fault Location for Double-Circuit Lines Connected to Power Electronics-Based Sources - Neethu George; O. D. Naidu; Ashok Kumar Pradhan (IEEE Access)
Double-circuit transmission line installations are rising due to their enhanced reliability, power transfer capability and operational flexibility, particularly in grids with significant share of power electronics-based sources. Reliable protection of these lines ensures the isolation of faulty sections, while precise fault location enables maintenance teams to quickly address the cause, thereby facilitating faster restoration and avoiding unnecessary curtailment of the clean power. Existing single-ended protection and fault location methods have limitations when applied to such double-circuit lines connected to power-electronics based renewable energy sources, mainly due to the source-dependent, variable, and controlled nature of their transient response. In this paper, limitations of existing methods when applied to such systems are demonstrated with several illustrative cases, and a reliable single-ended protection and an accurate fault location method are proposed. Protection requires the faulted line to be identified; this is achieved based on the polarity of the angle of an operating quantity evaluated at two extreme boundaries of the zone of protection. The operating quantity is defined as the apparent power flowing into the fault resistance path expressed as the function of fault location on the line of interest. Further, based on the same principle, accurate fault location is also identified without any additional measurement or complex calculations. Source-agnostic performance is accomplished through observability of the remote end using locally measured healthy line current. The proposed method is verified for multiple system configurations with power electronics-based resources including system with 100% such sources. The method is validated using experimental and field data and it is found to be reliable. Performance comparison with traditional distance, and existing single-ended protection and fault location methods for lines connected with power electronics-based resources are also conducted and improved performance is demonstrated.